Gambaran Kepatuhan Pasien dengan Penyakit Ginjal Kronis dalam Menjalani Hemodialisis di RSUD Prof.Dr.W.Z. Johanes - Ishak O. Terru Leo; Tadeus A.L. Regaletha; Sigit Purnawan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Hemodialysis is a tool that patients with chronic kidney disease (CKD) need to replace damaged kidney function. Compliance with hemodialysis plays an important role in the patient's health condition. Since 2021, the number of hemodialysis patients at RSUD Prof.DR.W.Z. Johanes, from 108 patients to around 85 patients remaining in 2022. This study aims to provide an overview of CKD patients' compliance in undergoing hemodialysis at RSUD Prof.DR.W.Z. John. This type of research is qualitative with a case study approach. Eight key informants and two supporting informants using purposive sampling. The research results showed that generally, hemodialysis compliance among informants was good. Predisposing factors, knowledge about hemodialysis and its risks, motivation to comply with hemodialysis such as the hope of health, not wanting to give up, want to work, and also the desire to still live with the family as well as belief in the benefits of hemodialysis encouraging informants to be more compliant. Supporting factors such as completeness of facilities and affordability of access to services encourage more optimal hemodialysis. Reinforcing factors such as emotional, instrumental, and information support provided by family and health workers increase informants' compliance with hemodialysis. Hemodialysis units can improve and maintain the quality of hemodialysis facilities and services. Existing health workers can increase patient knowledge and motivation by maintaining positive communication during the hemodialysis process. The family can be a positive companion for the fulfillment of hemodialysis patients. Hemodialysis patients must maintain and improve their physical and mental condition.